Dicyano-Substituted Diazaacenes - Müller, Matthias; Beglaryan, Stella S.; Koser, Silke; Hahn, Sebastian; Tverskoy, Olena; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2017)
Herein, we report the synthesis, spectroscopic, and structural properties of novel 2,3-dicyano-substituted azaacenes containing three to six annelated rings as a framework. The targets were prepared by Pd-catalyzed coupling of diamino-bis(tri-isopropylsilylethynyl)benzene, -naphthalene, and -anthracene with either 4,5-dibromophthalonitrile or 6,7-dibromonaphthalene-2,3-dicarbonitrile into the respective N,N′-dihydrodiazaacenes. Oxidation with MnO2 or PbO2 furnishes the dicyano-substituted diazaacenes in reasonable to good yields. An exception is the diazahexacene, where the N,N′-dihydrodiazaacene is difficult to oxidize. Most of the targets could be crystallized and pack in isolated pairs, stacks, and brick-wall motifs. The n-type behavior of these molecules was illustrated in a proof-of-concept organic field-effect transistor, showing mobilities up to 7×10−3 cm2 V−1 s−1.